Peer Teaching to Improve the Social Interaction of Students with Special Needs in Inclusive Elementary Schools - Mufid Zaiq Ja'far; Wahdan Najib Habiby (Lembaga Bale Literasi, 2026)
This study aims to analyze the effect of the peer teaching approach on the social interaction of children with special needs in inclusive elementary schools. The background of this study is based on the low level of social interaction among students with special needs, including limitations in communication, participation, and cooperation with peers. The peer teaching approach is considered effective in creating a more equal and supportive learning environment that can encourage social interaction. This study employed a quantitative approach using an experimental method with a one-group pretest-posttest design. The subjects of this study were children with special needs at SD Muhammadiyah Program Unggulan Gedongan who were selected using a purposive sampling technique. Data were collected through observations of social interaction before and after the implementation of peer teaching. The results showed that there was an improvement in the social interaction of children with special needs after the implementation of peer teaching, as indicated by increased communication, cooperation, and participation in learning activities. Therefore, peer teaching has a positive and significant effect and is effective in improving the social interaction of children with special needs in inclusive elementary schools.